Environmental Pollution in Russia: Lessons for Nigeria - Aigbovia, Kessington (Àgídìgbo: ABUAD Journal of the Humanities, 2016)
Environmental protection has been an important international issue since the past quarter of a century. The need to approach development with consideration for a healthy environment has been increasingly recognised as environmental problems such as global warming have caused extensive global concern. Nigeria has had its own share of environmental pollution. It has been a major cause of instability in the Niger Delta, where the youths have protested the destruction of their means oflivelihood. This paper examines the nature and impact of environmental pollution in Russia and the lessons that Nigeria can learn from the Russian experience. The paper also examines contemporary national developmental issues in Nigeria and the place of environmental protection in Nigeria’s public policy.